Happiness for humans - Russell, Daniel C. (Oxford : Oxford University Press, 2013)
The author presents a new account of happiness and how to live a good life. He returns to the ancient tradition of eudaimonism to argue that happiness is a life of activity that involves acting for the sake of ends we can live for. It is not only fulfilling for us as humans and individuals, but inseparable from what makes us who we are.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Happiness; Contentment; Hedonism